Tinjauan Yuridis Kegunaan Sidik Jari Dalam Proses Penyidikan(Studi kasus di Polresta Surakarta) - ERLANI, KIKY, Hartanto, S.H., M.Hum (2017)
In uncovering a case, the task of the investigator is required in conducting the investigation and identification to search for and collect evidence, the evidence makes it clear that no criminal case and in order to find the suspects. It is known that the role of identification in the investigation is to find evidence (fingerprints talent, face) in the process of criminal investigation scientifically and as an expert witness in the trial can be justified by the law in evidence during the trial. The fingerprints is a useful means of identification in the disclosure of a criminal offense or a comparison that can be made by the investigator, it is known that human fingerprints are not the same.